Ambivalent Modernities: Foucault’s Iranian Writings Reconsidered - Corey McCall (Foucault Studies, 2013)
This essay reconsiders Foucault’s writings on the Iranian Revolution in the context of his thought during 1977-1979. The essay defends three related claims: (1) Foucault does not turn away from power toward ethics as many scholars have claimed, (2) Careful interpretation of the texts on the Iranian Revolution will help us to better understand Foucault’s essays and lecture courses from this period (in particular, the relationship between political spirituality and counter-conduct), and (3) During this period Foucault is working on conceptualizing modernity as a multivalent set of practices—some that reinforce power relations and some that resist them.